Model Tata Kelola Knowledge Sharing Dalam Meningkatkan Kinerja Organisasi Perpustakaan Perguruan Tinggi - Nasrul Makdis; Zulfitri Zulfitri; Rusdi Aras; Deka Putri Naryanti; Lili Sudria Wenny (IQRA`: Jurnal Perpustakaan dan Informasi, 2026)
University libraries are required to continuously improve their organizational performance in response to the rapid development of information technology and the increasing complexity of academic community needs. One strategy that can be adopted is the implementation of knowledge sharing that is systematically managed through an effective governance system. This article aims to analyze a knowledge sharing governance model as an effort to enhance the organizational performance of university libraries. The research employs a qualitative approach using a literature review of scholarly journals, books, and various publications relevant to knowledge sharing, organizational governance, and library performance. The findings indicate that knowledge sharing governance supported by effective leadership, a collaborative organizational culture, human resource competencies, the utilization of information technology, and continuous evaluation contributes positively to improving library organizational performance. In conclusion, the implementation of an integrated knowledge sharing governance model is able to enhance work effectiveness, service quality, and innovation in university libraries.